A porous hard carbon material prepared from rubber scraps and a preparation method and application thereof

CN122977355APending Publication Date: 2026-10-27ENERGY RESOURCES INST HEBEI ACADEMY OF SCI +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611211314.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,纯橡胶直接炭化所得的碳材料比表面积小、孔隙结构单一,储钠容量与倍率性能均不理想,必须通过活化改性与结构优化才能满足电池负极的性能要求

Benefits of technology

[0028]本发明提供了一种利用橡胶边角料制备的多孔硬碳材料,所述碳材料由改性橡胶边角料粉末、壳聚糖、氯化镁、氯化锌制得,经实验验证,本发明得到的碳材料具有高微孔占比、良好的电池容量、高稳定性,高0.5C/0.1C放电容量保持率和高1.0C/0.1C放电容量保持率,具有良好的工业前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of carbon material, in particular to a kind of porous hard carbon material prepared from rubber scraps and its preparation method and application.The preparation method is specifically as follows:A.with the mass ratio of 8~12:10:3~7:3~7, modified rubber scrap powder, chitosan, magnesium chloride and zinc chloride are used as raw materials, glacial acetic acid and water are added to the raw materials, and ball milling is carried out at 200~800r / min for 3~5h to obtain a gel;B.the gel is frozen at-60~‑100℃ for 10~15h, then vacuum dried at room temperature for 36~72h to obtain dry gel, the obtained dry gel is calcined at 1200~1500℃ for 1~3h under protective atmosphere, and after washing and drying, porous hard carbon material is obtained.The carbon material obtained by the present application has high micropore ratio, good battery capacity, stability, high 0.5C / 0.1C discharge capacity retention rate and high 1.0C / 0.1C discharge capacity retention rate, and has good industrial prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon materials technology, specifically to a porous hard carbon material prepared using rubber scraps, its preparation method, and its application. Background Technology

[0002] Among the developed sodium-ion battery anode material systems, hard carbon materials are currently recognized as the most commercially promising sodium-ion battery anode materials due to their low sodium intercalation potential, high reversible capacity, and excellent structural tolerance. Existing hard carbon materials are mostly derived from precursors such as biomass, phenolic resins, and asphalt, and generally suffer from the technical bottleneck of difficult pore structure control: the pore structure of most hard carbon materials cannot adequately provide active sites and diffusion channels for sodium ion storage, and also increases the side reaction interface between the material and the electrolyte. This leads to rapid capacity decay and insufficient long-cycle stability under high-current charge-discharge conditions, making it difficult to meet the application requirements of high-power energy storage scenarios.

[0003] Meanwhile, the rubber processing industry generates a massive amount of rubber scrap waste annually. Traditional landfill and incineration methods not only cause serious resource waste but also lead to environmental pollution problems such as air and soil contamination. Preparing carbon-based functional materials from waste rubber through high-temperature carbonization is an important technological path to achieve high-value and resource-based utilization of waste rubber. However, carbon materials obtained from the direct carbonization of pure rubber have a small specific surface area and a simple pore structure, resulting in unsatisfactory sodium storage capacity and rate performance. Activation modification and structural optimization are necessary to meet the performance requirements of battery anodes.

[0004] The inventors' team has conducted relevant research on porous hard carbon materials prepared using rubber scraps and applied for a Chinese patent with application number 202511216386.4. This application provides a porous hard carbon material made from aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate. This invention is a follow-up study carried out against this background, in order to obtain a porous hard carbon material with better performance. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a porous hard carbon material with high micropore ratio, good battery capacity, high stability and high 0.5C and 1.0C discharge retention rate.

[0006] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] Technical Topic 1

[0008] A method for preparing porous hard carbon material using rubber scraps, the key of which includes the following steps:

[0009] A. Using modified rubber scrap powder, chitosan, magnesium chloride, and zinc chloride in a mass ratio of 8~12:10:3~7:3~7 as raw materials, glacial acetic acid and water are added to the raw materials, and the mixture is ball-milled at 200~800 r / min for 3~5 h to obtain a gel;

[0010] B. Freeze the gel at -60~-100℃ for 10~15h, then vacuum dry at room temperature for 36~72h to obtain a dry gel. Calcinate the obtained dry gel at 1200~1500℃ for 1~3h under a protective atmosphere. After washing and drying, a porous hard carbon material is obtained.

[0011] The modified rubber scrap powder is obtained by dispersing rubber scrap powder in concentrated sulfuric acid, adding potassium permanganate at 0-5℃ for modification, and then separating the solid and liquid, washing, and drying after modification.

[0012] As a further improvement of the present invention, rubber scrap refers to waste vulcanized rubber materials generated during the production, processing and finishing of rubber products that are not ultimately used. Specific forms include, but are not limited to: cutting scraps, stamping edges, flash, burrs; defective products (defective products, scrapped products); and mold overflow (rubber edges).

[0013] As a further improvement of the present invention, the rubber scrap is vulcanized natural rubber scrap.

[0014] As a further improvement of the present invention, the preparation method of the modified rubber scrap powder is as follows: rubber scrap powder ground to pass through a 60-200 mesh sieve is added to concentrated sulfuric acid and mechanically stirred. Under the condition of 0-5℃, a potassium permanganate solution with a mass fraction of 5-20wt% is added dropwise. After the addition is completed, stirring is continued at 0-5℃ for 3-5 hours. The mixture is then filtered, washed, and dried to obtain the modified rubber scrap powder.

[0015] The mass-to-volume ratio of the rubber scrap powder to concentrated sulfuric acid is 1g:10-30ml;

[0016] The mass-to-volume ratio of the rubber scrap powder to the potassium permanganate solution is 1g:5-20ml.

[0017] As a further improvement of the present invention, the concentrated sulfuric acid is 98wt% concentrated sulfuric acid.

[0018] As a further improvement of the present invention, the mechanical stirring rate is 50-200 r / min.

[0019] As a further improvement of the present invention, the ratio of chitosan, glacial acetic acid and water in step A is: 5g: 0.5~2ml: 8~20ml.

[0020] As a further improvement of the present invention, the heating rate during the calcination process in step B is 4-6℃ / min.

[0021] As a further improvement of the present invention, the vacuum degree of vacuum drying in step B is less than 100 Pa.

[0022] As a further improvement of the present invention, the protective gas in step B is nitrogen, helium or argon.

[0023] Technical Theme Two

[0024] A porous hard carbon material prepared by a method for preparing porous hard carbon material using rubber scraps as described in Technical Subject 1.

[0025] Technical Theme 3

[0026] Application of a porous hard carbon material as described in Technical Subject 2 in sodium-ion batteries.

[0027] The beneficial effects of adopting the above technical solution are as follows:

[0028] This invention provides a porous hard carbon material prepared from rubber scraps. The carbon material is made from modified rubber scrap powder, chitosan, magnesium chloride, and zinc chloride. Experimental verification shows that the carbon material obtained by this invention has a high micropore ratio, good battery capacity, high stability, high 0.5C / 0.1C discharge capacity retention rate, and high 1.0C / 0.1C discharge capacity retention rate, and has good industrial prospects. Attached Figure Description

[0029] Figure 1 This is a scanning electron microscope image of the carbon material prepared in Example 1 of this invention;

[0030] Figure 2 This is a transmission electron microscope image of the carbon material prepared in Example 1 of the present invention. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of the present invention clearer, the invention will be described clearly and completely below in conjunction with specific embodiments.

[0032] The chitosan used in this invention was purchased from Aladdin Reagents, catalog number: C1516215;

[0033] The rubber scraps are vulcanized natural rubber scraps provided by Hebei Baoli Engineering Equipment Co., Ltd. The base material is natural rubber, which has undergone vulcanization treatment and is the processing waste generated during the company's production process.

[0034] Preparation Example 1

[0035] 10g of rubber scrap powder, ground to pass through a 100-mesh sieve, was added to 200ml of 98wt% concentrated sulfuric acid and mechanically stirred at 100r / min. Under 0-5℃ conditions, 100ml of 10wt% potassium permanganate solution was added dropwise. After the addition was completed, stirring was continued at 0-5℃ for 4h. The mixture was then filtered, washed, and dried to obtain modified rubber scrap powder.

[0036] Preparation Example 2

[0037] 10g of rubber scrap powder, ground to pass through a 60-mesh sieve, was added to 300ml of 98wt% concentrated sulfuric acid and mechanically stirred at 200r / min. Under 0-5℃ conditions, 200ml of 5wt% potassium permanganate solution was added dropwise. After the addition was completed, stirring was continued at 0-5℃ for 5h. The mixture was then filtered, washed, and dried to obtain modified rubber scrap powder.

[0038] Preparation Example 3

[0039] 10g of rubber scrap powder, ground to pass through a 200-mesh sieve, was added to 100ml of 98wt% concentrated sulfuric acid and mechanically stirred at 50r / min. 50ml of 20wt% potassium permanganate solution was added dropwise at 0-5℃. After the addition was complete, stirring was continued at 0-5℃ for 3h. The mixture was then filtered, washed, and dried to obtain modified rubber scrap powder.

[0040] Preparation Example 4

[0041] 10g of rubber scrap powder, ground to pass through a 100-mesh sieve, was added to 200ml of 98wt% concentrated sulfuric acid and mechanically stirred at 100r / min. 100ml of water was added dropwise at 0-5℃. After the addition was complete, stirring was continued at 0-5℃ for 4h. The mixture was then filtered, washed, and dried to obtain modified rubber scrap powder.

[0042] Example 1

[0043] A. Using 10g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain a gel.

[0044] B. Freeze the gel at -80℃ for 12h, then vacuum dry it at room temperature under a vacuum degree <10Pa for 48h to obtain a dry gel. The obtained dry gel is heated to 1400℃ at 5℃ / min under a nitrogen atmosphere and calcined at 1400℃ for 2h. It is then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, a porous hard carbon material is obtained.

[0045] Example 2

[0046] A. Using 10g of modified rubber scrap powder obtained in Preparation Example 2, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 1ml of glacial acetic acid and 16ml of deionized water were added to the raw materials, and the mixture was ball-milled at 200r / min for 5h to obtain a gel.

[0047] B. Freeze the gel at -60℃ for 15h, then vacuum dry it at room temperature under a vacuum degree <10Pa for 36h to obtain a dry gel. The obtained dry gel is heated to 1200℃ at 4℃ / min under a nitrogen atmosphere and calcined at 1200℃ for 3h. It is then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, a porous hard carbon material is obtained.

[0048] Example 3

[0049] A. Using 10g of modified rubber scrap powder obtained in Preparation Example 3, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 4ml of glacial acetic acid and 40ml of deionized water were added to the raw materials, and the mixture was ball-milled at 800r / min for 3h to obtain a gel.

[0050] B. Freeze the gel at -100℃ for 10h, then vacuum dry it at room temperature under a vacuum degree <10Pa for 72h to obtain a dry gel. The obtained dry gel is heated to 1500℃ at 6℃ / min under a nitrogen atmosphere and calcined at 1500℃ for 1h. It is then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, a porous hard carbon material is obtained.

[0051] Example 4

[0052] A. Using 8g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, 3g of magnesium chloride, and 7g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain a gel.

[0053] B. Freeze the gel at -80℃ for 12h, then vacuum dry it at room temperature under a vacuum degree <10Pa for 48h to obtain a dry gel. The obtained dry gel is heated to 1400℃ at 5℃ / min under a nitrogen atmosphere and calcined at 1400℃ for 2h. It is then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, a porous hard carbon material is obtained.

[0054] Example 5

[0055] A. Using 12g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, 7g of magnesium chloride, and 3g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain a gel.

[0056] B. Freeze the gel at -80℃ for 12h, then vacuum dry it at room temperature under a vacuum degree <10Pa for 48h to obtain a dry gel. The obtained dry gel is heated to 1400℃ at 5℃ / min under a nitrogen atmosphere and calcined at 1400℃ for 2h. It is then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, a porous hard carbon material is obtained.

[0057] Comparative Example 1

[0058] A. Using 10g of the modified rubber scrap powder obtained in Preparation Example 1, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain the ball-milled product.

[0059] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1400°C at 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0060] Comparative Example 2

[0061] A. Using 10g chitosan, 5g magnesium chloride, and 5g zinc chloride as raw materials, add 2ml glacial acetic acid and 20ml deionized water to the raw materials, and ball mill at 400r / min for 4h to obtain the ball-milled product.

[0062] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1400°C at 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0063] Comparative Example 3

[0064] A. Using 10g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, and 10g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain the ball-milled product.

[0065] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1400°C at 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0066] Comparative Example 4

[0067] A. Using 10g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, and 10g of magnesium chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain the ball-milled product.

[0068] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1400°C at 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0069] Comparative Example 5

[0070] A. Using 10g of rubber scrap powder that has passed through a 100-mesh sieve, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, add 2ml of glacial acetic acid and 20ml of deionized water to the raw materials, and ball mill at 400r / min for 4h to obtain the ball milled product.

[0071] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1400°C at 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0072] Comparative Example 6

[0073] A. Using 10g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain the ball-milled product.

[0074] B. The ball-milled product is vacuum-dried for 48 hours under a vacuum degree <10 Pa. The dried product is then heated to 1400°C at a rate of 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. After washing three times with 5wt% hydrochloric acid solution and then three times with deionized water, the porous hard carbon material is obtained after drying.

[0075] Comparative Example 7

[0076] A. Using 10g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain the ball-milled product.

[0077] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1000°C at 5°C / min under a nitrogen atmosphere and calcined at 1000°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, a porous hard carbon material was obtained.

[0078] Comparative Example 8

[0079] A. Using 10g of the modified rubber scrap powder obtained in Preparation Example 4, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain the ball-milled product.

[0080] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1400°C at 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0081] Comparative Example 9

[0082] A. Using 5g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain the ball-milled product.

[0083] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1400°C at 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0084] Comparative Example 10

[0085] A. Using 15g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 2ml of glacial acetic acid and 20ml of deionized water were added to the raw materials, and the mixture was ball-milled at 400r / min for 4h to obtain the ball-milled product.

[0086] B. The ball-milled product was frozen at -80°C for 12 hours, then vacuum dried at room temperature under a vacuum of <10 Pa for 48 hours. The dried product was heated to 1400°C at 5°C / min under a nitrogen atmosphere and calcined at 1400°C for 2 hours. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0087] Comparative Example 11

[0088] A. Using 10g of modified rubber scrap powder obtained in Preparation Example 1, 10g of chitosan, 5g of magnesium chloride, and 5g of zinc chloride as raw materials, 20ml of deionized water was added to the raw materials, and the mixture was ball-milled at 400r / min for 4h.

[0089] B. The ball-milled product was frozen at -80℃ for 12h, then vacuum dried at room temperature under a vacuum degree <10Pa for 48h. The resulting dry ball-milled product was heated to 1400℃ at 5℃ / min under a nitrogen atmosphere and calcined at 1400℃ for 2h. It was then washed three times with 5wt% hydrochloric acid solution and three times with deionized water. After drying, porous hard carbon material was obtained.

[0090] Example 1

[0091] Preparation of working electrode: The hard carbon materials prepared in Examples 1-5 and Comparative Examples 1-11 were mixed with acetylene black and polyvinylidene fluoride at a mass ratio of 8:1:1 and ground. Then, N-methylpyrrolidone was added dropwise while grinding to prepare a slurry. The slurry was evenly coated on copper foil and heated to dry to obtain the working electrode.

[0092] Preparation of electrolyte: The electrolyte is prepared in a glove box as a mixed solution of EC:DMC:EMC with a volume ratio of 1:2:2, and the concentration of solute NaPF6 is 1.5M.

[0093] Test: The glass microfiber diaphragm, sodium metal sheet as reference electrode, working electrode, CR2032 battery casing, and gasket were placed in an argon-filled glove box to assemble a half cell.

[0094] 1. Under a high current of 10A / g, the assembled button cell was subjected to charge-discharge cycle testing using the LAND CT2001A battery testing system. Stability refers to the battery capacity retention rate after 1000 cycles.

[0095] 2. After the battery is assembled, allow it to stand at a constant temperature of 25°C. Set the charge / discharge cutoff voltage to 0V~2V. After the battery interface stabilizes, perform constant current charge / discharge tests on the assembled button battery at current rates of 0.1C, 0.5C, and 1.0C. Record the discharge specific capacity at each rate, which corresponds to the battery capacity at 0.1C, 0.5C, and 1.0C, respectively. Calculate the capacity retention rate. The charge / discharge rate C mentioned in this invention is based on the specific capacity of the electrode sheet at the first constant current discharge at 0.1C.

[0096] Table 1

[0097]

[0098]

[0099] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing porous hard carbon material using rubber scraps, characterized in that, Includes the following steps: A. Using modified rubber scrap powder, chitosan, magnesium chloride, and zinc chloride in a mass ratio of 8~12:10:3~7:3~7 as raw materials, glacial acetic acid and water are added to the raw materials, and the mixture is ball-milled at 200~800 r / min for 3~5 h to obtain a gel; B. Freeze the gel at -60~-100℃ for 10~15h, then vacuum dry at room temperature for 36~72h to obtain a dry gel. Calcinate the obtained dry gel at 1200~1500℃ for 1~3h under a protective atmosphere. After washing and drying, a porous hard carbon material is obtained. The modified rubber scrap powder is obtained by dispersing rubber scrap powder in concentrated sulfuric acid, adding potassium permanganate at 0-5℃ for modification, and then separating the solid and liquid, washing, and drying after modification.

2. The preparation method according to claim 1, characterized in that, The rubber scraps are vulcanized natural rubber scraps.

3. The preparation method according to claim 1, characterized in that, The modified rubber scrap powder is prepared as follows: rubber scrap powder ground to pass through a 60-200 mesh sieve is added to concentrated sulfuric acid and mechanically stirred. Under the condition of 0-5℃, a potassium permanganate solution with a mass fraction of 5-20wt% is added dropwise. After the addition is completed, stirring is continued at 0-5℃ for 3-5 hours. The mixture is then filtered, washed, and dried to obtain the modified rubber scrap powder. The mass-to-volume ratio of the rubber scrap powder to concentrated sulfuric acid is 1g:10-30ml; The mass-to-volume ratio of the rubber scrap powder to the potassium permanganate solution is 1g:5-20ml.

4. The preparation method according to claim 3, characterized in that, The mechanical stirring rate is 50-200 r / min.

5. The preparation method according to claim 1, characterized in that, The ratio of chitosan, glacial acetic acid, and water used in step A is: 5g: 0.5~2ml: 8~20ml.

6. The preparation method according to claim 1, characterized in that, The heating rate during the calcination process in step B is 4-6℃ / min.

7. The preparation method according to claim 1, characterized in that, The vacuum degree of vacuum drying in step B is less than 100 Pa.

8. The preparation method according to claim 1, characterized in that, In step B, the protective gas is nitrogen, helium, or argon.

9. A porous hard carbon material prepared by the method for preparing porous hard carbon material using rubber scraps as described in any one of claims 1-8.

10. The application of the porous hard carbon material as described in claim 9 in a sodium-ion battery.

Citation Information

Patent Citations

  • Aspartic acid-based porous hard carbon material as well as preparation method and application thereof

    CN120903477A